Pengaruh Model Problem Based Learning dan Discovery Learning Berbantuan Media ISpring Presenter terhadap Hasil Belajar - Masitah Salsabila; Hafni Indriati Nasution (Lembaga Pengembangan Kinerja Dosen, 2023)
This study aims to determine differences instudent learning outcomes in SMA Negeri 18 Medan. The population in this study were all Class XI IPA consisting of five classes. The sample in this study was taken randomly and selected two classes, namely Class XI IPA 1 and class XI IPA 2 was used as the experimental class 1 and 2 with the PBL and DL model. There are two instruments used in this study, namely the test instrument and the non-test instrument. The test instrument for measuring learning outcomes is in the form of multiple choice of 20 valid and reliable questions.. Data were analyzed by independent sample t test. The results showed that for the experimental class 1: learning outcomes 83.3 ± 7.8. While the experimental class 2: learning outcomes 76.0 ± 11.01. From the statistical test it was obtained sig for learning outcomes sig (0.001) < α (0.05) H0 was rejected and Ha was accepted, as well as the learning outcomes obtained value sig (0.000) < α (0.05) and sig (0.001) < α (0.05) in experimental class 1 and 2 respectively. Thus, it can be concluded that there are significant differences in learning outcomes.